Feasibility, acceptance and impact of Team-based Learning in Neurology: a pilot study - Brich, Jochen (German Medical Science GMS Publishing House, 2013)
Background/Goal: Neurology is rated as one of the most difficult specialties by medical students, as well as by medical practitioners in other areas. Team-based learning (TBL) as a method of active and group-based learning seems to be a suitable method to achieve greater learning success and a better understanding of neurology. Methods: The TBL neurology course was designed as a supplemental program within the regular neurology course for third-year medical students. This supplemental course consisted of six 90-minute units as a pilot study during the 2011-12 winter semester and was evaluated in terms of time and effort. The acceptance of the TBL concept in general, as well as of the TBL neurology course in particular, was assessed using written evaluations. The results of the final exam were analyzed with regard to participation in TBL and the content imparted therein. Results: The preparation time was approximately 8 hours per unit. The implementation was without difficulty. The high rate of regular attendance and the consistently very positive evaluation results indicated a high acceptance of the TBL concept in general, as well as of the TBL neurology course in particular. TBL participants displayed better results on the final exam in topics also covered in the TBL units. Conclusion: The resulting achievement of a subjectively better understanding and a simultaneously higher level of interest in neurology justified the one-time, relatively intense preparation effort for TBL. The high acceptance among students inexperienced in teamwork suggests an unproblematic transfer to other preclinical or clinical courses. The impact on measurably improved results in clinical reasoning and problem-solving skills should be further investigated in the context of controlled studies.